THE INFLUENCE OF ZEN BUDDHISM ON THE FORMATION OF REALISM IN JAPANESE CULTURE: FROM SIMPLICITY TO UNIVERSALITY - Анатолій МЕЛЕЩУК (Епістемологічні дослідження у філософії, соціальних і політичних науках)
This article explores the profound influence of Zen Buddhism on the formation of Japanese aesthetics, focusing on key concepts such as simplicity (kanso), naturalness (shibumi), and impermanence (mujo). Zen realism, characterized by the acceptance of reality without subjective embellishments, is examined as a foundational principle that shaped not only Japanese cultural identity but also a universal aesthetic language. The study highlights the philosophical tenets of Zen, including the principles of «non-duality» (fuju) and «direct intuition» (jikan), which guide the perception of reality as it is and foster a unique artistic and cultural worldview. Relevance: In the context of globalization and cultural exchange, the Zen-inspired Japanese approach to aesthetics offers valuable insights into contemporary issues of sustainability, mindfulness, and design thinking. The enduring appeal of Japanese minimalism in modern art, architecture, and design underscores the universality and adaptability of Zen principles, making this topic highly pertinent for cross-cultural studies and global artistic dialogues. Objective: The purpose of this study is to investigate how Zen Buddhist values influenced the development of Japanese aesthetics and contributed to creating a universal artistic and philosophical framework. Tasks: To achieve this objective, the article: - Analyzes the philosophical underpinnings of Zen realism in shaping the perception of reality. - Explores the aesthetic principles of simplicity (kanso), naturalness (shibumi), and impermanence (mujo) in traditional and modern Japanese art. - Examines the impact of Zen-inspired aesthetics on contemporary global design and architecture. The study demonstrates that the pursuit of simplicity, rooted in Zen practice, transcends cultural boundaries and has become a universal language in the realms of art and design. Examples include Tadao Ando’s architecture, which embodies harmony between light, space, and void, and the minimalist design philosophy of brands like Muji, which resonates globally. The analysis also underlines the role of Zen aesthetics in fostering ecological awareness and a deeper connection to the present moment, aligning with contemporary global challenges. The article concludes by emphasizing the potential of Zen-inspired aesthetics to serve as a universal cultural category, capable of bridging diverse traditions and promoting cross-cultural dialogue. Future research directions include examining Zen principles as a framework for addressing ecological, social, and philosophical issues in an increasingly interconnected world.